2009
DOI: 10.1007/s00221-009-1907-1
|View full text |Cite
|
Sign up to set email alerts
|

Tactile perception of roughness: raised-dot spacing, density and disposition

Abstract: Recently, we showed that tactile speed estimates are modified by the spatial parameters of moving raised-dot surfaces, specifically dot spacing but not dot disposition (regular, irregular) or density. The purpose of this study was to determine the extent to which tactile roughness perception resembles tactile speed with respect to its dependence and/or independence of the spatial properties of raised-dot surfaces. Subjects scaled the roughness of surfaces displaced under the finger. Dot spacing (centre-to-cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 19 publications
9
26
0
Order By: Relevance
“…For the P1 series, the first half (5 cm) of the segment had a longitudinal SP of 1.5 mm; dot spacing was either the same (segment 1) or increased on the second half of the surface (segments 2-4: a, 3.5, 5.5, 7.5 mm; b, 4.5, 6.5, 8.5 mm). These surfaces covered a wide range of SPs across which humans show a linear increase in roughness (Dépeault et al 2009;Meftah et al 2000;Sutu et al 2013) and extend the ranges studied previously, both in this laboratory (Chapman and Meftah 2005;Jiang et al 1997;Meftah et al 2002Meftah et al , 2009Tremblay et al 1996) and elsewhere (Darian-Smith et al 1982;Burton 1988, 1991a).…”
Section: Textured Surfacessupporting
confidence: 80%
See 4 more Smart Citations
“…For the P1 series, the first half (5 cm) of the segment had a longitudinal SP of 1.5 mm; dot spacing was either the same (segment 1) or increased on the second half of the surface (segments 2-4: a, 3.5, 5.5, 7.5 mm; b, 4.5, 6.5, 8.5 mm). These surfaces covered a wide range of SPs across which humans show a linear increase in roughness (Dépeault et al 2009;Meftah et al 2000;Sutu et al 2013) and extend the ranges studied previously, both in this laboratory (Chapman and Meftah 2005;Jiang et al 1997;Meftah et al 2002Meftah et al , 2009Tremblay et al 1996) and elsewhere (Darian-Smith et al 1982;Burton 1988, 1991a).…”
Section: Textured Surfacessupporting
confidence: 80%
“…1 (Meftah et al 2000): subjective roughness showed a monotonic increase across a wide range of dot spacings (1.5-8.5 mm SP), with identical results obtained when scanning speed was doubled on a trialby-trial basis. Similar monotonic relations between roughness and SP are obtained using nonperiodically disposed raised dots (Dépeault et al 2009) and tetragonal arrays of raised dots (Sutu et al 2013). Taken together, the critical factor for subjective roughness intensity is the spacing between raised dots in the direction of the scan, and any neuronal code needs to reflect this.…”
supporting
confidence: 61%
See 3 more Smart Citations